Juno Magnetometer Observations at Ganymede: Comparisons With a Global Hybrid Simulation and Indications of Magnetopause Reconnection. Issue 23 (12th December 2022) - Romanelli, N.; DiBraccio, G. A.; Modolo, R.; Connerney, J. E. P.; Ebert, R. W.; Martos, Y. M.; Weber, T.; Espley, J. R.; Kurth, W. S.; Allegrini, F.; Valek, P.; Bolton, S. J.
Abstract: Juno's flyby of Ganymede on 7 June 2021, provides a unique opportunity to explore the moon's magnetosphere. By means of Magnetometer (MAG) observations and a hybrid numerical simulation, we provide a global description of this environment and analyze the upstream magnetopause in detail. In particular, LATMOS Hybrid Simulation results suggest Juno observed open (one foot‐point connected to Ganymede, the other to Jupiter) and closed magnetic field lines along its trajectory. Additionally, we determine that the upstream magnetopause location and orientation seen by Juno MAG are consistent with previous Galileo observations. We observe a non‐zero normal component of the magnetic field across the magnetopause, along with flux rope structures embedded within the boundary's current sheet. Both signatures are strong indicators that magnetic reconnection was occurring along Ganymede's magnetopause. Based on this crossing, we calculate a shear angle of ∼78° across the magnetopause, with a dimensionless reconnection rate of ∼0.12. Plain Language Summary: In this work we provide a global description of Ganymede's magnetosphere in the context of Juno's flyby and investigate one of its main magnetospheric boundaries, the upstream magnetopause. This is done by analyzing magnetic field observations and performing a hybrid numerical simulation. In particular, we find that the upstream magnetopause position and orientation seen by Juno Magnetometer are consistent with observations from the previous Galileo mission. We also find and investigate strong indicators of magnetic reconnection occurring along Ganymede's magnetopause, a physical process where magnetic energy is converted to kinetic and thermal energy, and particle acceleration. Key Points: LATMOS hybrid numerical simulation provides a global description of Ganymede's magnetosphere in the context of Juno's flyby We find the upstream magnetopause location and orientation based on Juno Magnetometer data are consistent with previous Galileo observations The non‐zero magnetic field normal component across the magnetopause and detection of flux ropes are indicators of magnetic reconnection